Study the Behaviour of Using Steel Scrap in Concrete (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today the construction industry is in need  of finding cost effective materials for increasing the  strength of concrete structures. This project work emphasis  on the study of using steel scrap in the innovative  construction industry. Steel Scrap concrete is a concrete  containing fibrous material that is uniformly distributed  and casually oriented. This paper aims to have a  comparative study between turn fiber, binding wire and  steel nail in M25 concrete. The tests conducted were slump  test, compressive strength test, split tensile strength test  and for this concrete cubes, beams and cylinders were cast  and cured and tests were done at 3rd day, 7th day and 28th  day.
Keywords: LSSRC- Lathe steel scrap reinforced concrete; flexural strength; compressive strength; split tensile strength